Reducing Criminal Justice Involvement of Individuals Experiencing Homelessness and Mental Illness: perspectives of Frontline Practitioners - Roy, Laurence (Canadian journal of criminology and criminal justice, 2020)
Individuals experiencing both homelessness and mental illness have high rates of interaction with public safety and criminal justice institutions. Several cross-sector diversion programs have been developed over the past decades as alternatives to incarceration. Most of these initiatives rely on the commitment and expertise of frontline practitioners from different sectors and backgrounds. Th is research examines the perspectives of frontline practitioners regarding practices and policies that target justice involvement of individuals experiencing both homelessness and mental health issues in a Canadian urban context. Findings from focus groups with 55 participants drawn from the police, the community and public health and social services sectors indicate that frontline practitioners value and support close proximity in cross-sector action, while raising ethical and legal issues related to this type of practice. Participants also describe how exclusion from services for this population, lack of involvement from corrections, housing, and forensic mental health services, and ineffective use of involuntary treatment mechanisms shape and constrain frontline practice. Th e findings of this article give voice to the specific concerns of frontline service providers. Given these findings, we suggest potential strategies to better serve individuals who are identified as "harder to serve" but who might also benefit from diversion from the criminal justice system. (English)